Our Exciting Journey to ACT-451840 - Christoph Boss (Swiss Chemical Society, 2021)
We describe our work resulting in the selection of ACT-451840 ( 38 ) as a novel antimalarial drug with a novel mode of action. The compound was broadly characterized in vitro as well as in vivo in rat PK experiments as well as two different mouse malaria models. In the P. berghei infected mouse model cure could be achieved at oral doses of 300 mg/kg over 3 consecutive days. ACT-451840 was clinically investigated up to an experimental human malaria infection model, where therapeutic effects could be shown.